Green Extraction of Cellulose From Sago Trunk Bark of Kepulauan Meranti Via Deep Eutectic Solvents - Nafis Khuriyati; Wagiman Wagiman; Angga Pramana; Nanang Masruchin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Cellulose is a versatile biopolymer for high-value applications. This study investigates the use of eco-friendly Deep Eutectic Solvents (DES) to efficiently isolate cellulose from sago bark (Metroxylon spp.) under varying microwave irradiation times using a DES system. The isolation process using a DES solvent mixture of choline chloride and urea in a 1:2 molar ratio was irradiated with microwaves for 1, 2, and 3 minutes. The results showed that microwave irradiation time significantly affected the yield, purity, and ash content of the cellulose. The highest cellulose yield of 15.87% was obtained at 2 minutes, but decreased to 14.87% at 3 minutes due to cellulose component degradation over a longer period. Conversely, the highest cellulose purity achieved was 94.87% after 3 minutes of irradiation. The ash content of the obtained lignin ranged from 6.30% to 6.67%. FT-IR functional group analysis confirmed the successful cellulose purification, evidenced by the loss of most non-cellulose components (lignin and hemicellulose) and the appearance of characteristic cellulose peaks at wavelengths of 3302 cm?¹ (O-H elongation) and 1032 cm?¹ (C-O elongation). Overall, the combination of DES and microwaves proved effective in producing high-purity cellulose from sago bark waste. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action